2016
DOI: 10.1016/j.spmi.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal nanoparticles on porosification of silicon by metal induced etching (MIE)

Abstract: Porosification of silicon (Si) by metal induced etching (MIE) process have been studies here to understand the etching mechanism. The etching mechanism has been discussed on the basis of electron transfer from Si to metal ion (Ag + ) and metal to H 2 O 2 . Role of silver nanoparticles (AgNPs) in the etching process has been investigated by studying the effect of AgNPs coverage on surface porosity. A quantitative analysis of SEM images, done using Image J, shows a direct correlation between AgNPs coverage and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Our work gives stronger support to the ion re-deposition process since we are essentially looking at redox processes. The metal ions etching around the metal catalyst may also be the source of porosity creation in the etched Si, especially when there are unequal and varying etch rates in different microscopic regions5152. Such porosity generation was also observed in our work along the walls and beneath metal catalyst (see Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…Our work gives stronger support to the ion re-deposition process since we are essentially looking at redox processes. The metal ions etching around the metal catalyst may also be the source of porosity creation in the etched Si, especially when there are unequal and varying etch rates in different microscopic regions5152. Such porosity generation was also observed in our work along the walls and beneath metal catalyst (see Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…The step-by-step procedure for fabrication of SiNWs is given in the Supporting Information. The detailed etching mechanism of MIE has already been reported by our group in the literature . The surface and cross-sectional morphologies of the prepared samples were recorded using a scanning electron microscope (SEM; Supra55 Zeiss).…”
Section: Experimental Detailsmentioning
confidence: 99%
“…During the HNO 3 treatment strong oxide layer is formed on SiNSs, to remove this oxide layer induced by HNO 3 the samples are dipped again in HF solution. The details of MIE mechanism have been reported in the previous literature [22][23][24]. In order to confirms the wire like structures formed after etching, transmission electron microscopy (TEM) was carried out using TEM-Gatan model 636MA.…”
Section: Methodsmentioning
confidence: 99%
“…Besides certain disadvantages, the PCM has been used as the most widely used formulation when it comes to interpretation of the Raman scattering results obtained from low dimensional semiconductors especially elemental ones. In recent attempts to rectify the shortcomings of the PCM, Jia et al [21] have been reported in the previous literature [22][23][24]. In order to confirms the wire like structures formed after etching, transmission electron microscopy (TEM) was carried out using TEM-Gatan model 636MA.…”
Section: Introductionmentioning
confidence: 99%